PENGARUH AKUPRESUR PADA TITIK TAI CHONG DAN GUANYUAN TERHADAP PENURUNAN INTENSITAS NYERI HAID (DISMENORHEA) PADA REMAJA PUTRI - Dian Pangastuti; Mukhoirotin Mukhoirotin (Jurnal EDUNursing, 2018)
Menstrual pain (dysmenorrhea) is often experienced by women who is getting menstruation period and it can bother the daily activities. Non pharmacological treatments of dysmenorrhea are using acupressure in Tai Chong and Guanyuan Point. The purpose of this research was to know the difference between the effect of Tai Chong and Guanyuan Point to reduce the pain of dysmenorrhea intensity. The research design used Quasy Experiment with Pretest-Postest Design approach and the sampling used Purposive Sampling technique. The samples were consisted of 60 respondents of female teenagers in the Islamic Boarding School Dormitory of As’Adiyah Darul 'Ulum Jombang which fulfilled the inclusion and exclusion criteria. The instrument of measuring pain was using NRS, the data were analyzed by using Wilcoxon and Mann Whitney with α ≤ 0.05. The research results showed that there was an effect on the Tai Chong Point towards menstrual pain with a significant value of 0,000 (p < α) and there was an effect of acupressure on Guanyuan Point towards menstrual pain with a significant value of 0.000 (p < α). There was no difference between acupressure group of Tai Chong and Guanyuan Point with significant value 0.637 (p > α). Acupressure at Tai Chong and Guanyuan Points were effective to reduce dysmenorrhea intensity, clinically the reduction of dysmenorrhea intensity was higher with the acupressure of Tai Chong Point. Key words: acupressure, dysmenorrhea, adolescent girl